Binding characteristics to mosquito-larval midgut proteins of the cloned domain II-III fragment from the Bacillus thuringiensis Cry4Ba toxin - Seangdeun Moonsom (2018)
Receptor binding plays an important role in determining host specificity of the Bacillus thuringiensis Cry δ-endotoxins. Mutations in domains II and III have suggested the participation of certain residues in receptor recognition and insect specificity. In the present study, we expressed the cloned domain II-III fragment of Cry4Ba and examined its binding characteristics to mosquito-larval midgut proteins. The 43-kDa Cry4Ba-domain II-III protein over-expressed in Escherichia coli as inclusion bodies was only soluble when carbonate buffer, pH 10.0 was supplemented with 4M urea. After renaturation via stepwise dialysis and subsequent purification, the refolded domain II-III protein, which specifically reacts with anti Cry4Ba-domain III monoclonal antibody, predominantly exists as a β-sheet structure determined by circular dichroism spectroscopy. In vitro binding analysis to both histological midgut tissue sections and brush border membrane proteins prepared from susceptible Aedes aegypti mosquito-larvae revealed that the isolated Cry4Ba-domain II-III protein showed binding functionality comparable to the 65-kDa full-length active toxin. Altogether, the data present the 43-kDa Cry4Ba fragment comprising domains II and III that was produced in isolation was able to retain its receptor-binding characteristics to the target larval midgut proteins.